Simple Efficient Routes for the Preparation of Pyrazoleamines and Pyrazolopyrimidines: Regioselectivity of Pyrazoleamines Reactions with Bidentate Reagents - Moustafa Sherief Moustafa (Croatica Chemica Acta, 2016)
Simple and efficient routes for the preparation of 2-amino-5-phenyl-4,5-dihydrofuran-3-carbonitrile (12), 2-oxo-5-phenyl-tetrahydrofuran-3-carbonitrile (13) and the 3,5-diaminopyrazole derivative 2h were developed. The results of the reactivity profiles of 12 and 2h are reported and the previously investigated reaction of pyrazole-3,5-diamine (2b) with acrylonitrile to yield compound (31), a N-1 acylation product, is currently justified by using X-ray crystallographic analysis. Taken together, the observation of alkenes and alkynes substitution when reacting with 3,5-diaminopyrazole derivative 2h is explained by the terminal electron withdrawing group. This pattern of substitution is attributed to involvement of sterically unhindered electrophiles primarily at the N-1 position. This work is licensed under a Creative Commons Attribution 4.0 International License.